"Prevalencia de brucelosis bovina con la prueba de rosa de bengala en el Cantón El Empalme". - Meza Pauta, Jonathan Alex (2020)
Bovine brucellosis is a disease transmissible from animals to humans (zoonosis), caused by bacteria of the genus Brucella. In the present investigation the prevalence of bovine brucellosis (Brucella abortus) was determined by means of the pink bengal test in the Bromatology laboratory of the UTEQ campus "La María". We worked with 370 blood samples taken from the coccygeal vein of cattle farms corresponding to the north, south, east and west areas, the variables analyzed were presence of the disease, sex, age, provenance and breed of animals. The prevalence was 19.18%, giving a total of 28 positive animals, although these had no apparent clinical signs. Regarding sex, females are more susceptible to the disease, obtaining 27 (7.29%) positive cases and males 1 (0.27%) positive cases. Of the 370 bovine animals sampled, 13 (3.51%) of positive cases corresponded to crossbred breeds (Brahmán x Brown Swiss), Brahman x Holstein 9 (2.43%) positive cases, Girolando 3 (0.81%) positive cases, Jersey 2 (0.54 %) positive cases and Brahman 1 (0.27%) positive cases. Likewise, of the animals sampled, 2.97% of positive cases corresponded to animals aged 2-4 years, 2.43% to animals aged 5-7 years, and in animals aged 8-12 years, 2.16% of positive cases were obtained. It was determined that the economic losses caused by this disease is $ 750 dollars, therefore, it is concluded that it is necessary for the cattle farms in the El Empalme canton to have a health administration system that allows controlling and eradicating this disease that economically affects small, medium and large farms in the area, since the animal's health level is linked to the economy of livestock companies. Keywords: Bovine, Brucella, Rose Bengal ix